PEMBERDAYAAN KOPERASI SEKOLAH MENURUT SYARIAT ISLAM - Azwar Rahmat (JURNAL AGHNIYA, 2018)
Cooperative is a type of business entity consisting of persons or legal entities. The cooperative based its activities based on the principle of the people's economic movement based on the principle of kinship. Cooperative according to the 1945 Constitution article 33 paragraph 1 is a family effort with the aim of welfare of its members. Cooperatives are business institutions that are considered suitable to empower the small people. Cooperative values are also noble such as justice, togetherness, kinship, and community welfare. Some scholars regard the cooperative (Syirkah Ta'awuniyah) as a mudaraba agreement, which is a cooperation agreement between two or more people, on the one hand provides business capital, while the other party does business on the basis of profit sharing (sharing profit) according to the agreement, and in between the legitimate requirements of the mudaraba is to fix profits annually with a fixed percentage, for example 1% a year to one of the parties of the mudaraba. Sharia cooperative is a cooperative founded on the basis of Islamic law. The purpose of sharia cooperatives is to improve the welfare of members in particular and society in general and also to build a just economic order in accordance with the principles of Islam in this case is the citizens of the school. Keywords: School Cooperative, Islamic Shari'a.